Pengaruh Problem Based Learning Berbantuan Media Prezi Terhadap Hasil Belajar dan Kemampuan Berpikir Kritis Siswa Kelas XI MPLB SMK PGRI 2 Sidoarjo - Siti Aisyah; Siti Sri Wulandari (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This research aims to determine the effect of the Problem Based Learning (PBL) learning model assisted by Prezi media on the learning outcomes and critical thinking abilities of class XI MPLB students at SMK PGRI 2 Sidoarjo in the subject of Human Resource Management. The research method used is an experiment with a quasi experimental design. The type of design used is pre-test and post-test with non-equivalent control-group. The sample consisted of 45 students from class XI MPLB 1 as the experimental class and 45 students from class XI MPLB 2 as the control class. Research data was obtained from test results, observations, interviews and documentation. Data analysis techniques use normality tests, homogeneity tests, ngain tests, and hypothesis tests. The results of hypothesis testing on students' learning outcomes and critical thinking ability tests show sig. (2-tailed) with Equal variances assumed of 0.000 < 0.05. Based on the test results, it can be concluded that and are accepted, meaning that the Problem Based Learning (PBL) learning model assisted by Prezi media has an effect on students' learning outcomes and critical thinking skills.